Knowledge, Attitudes and Practices of Emergency Contraceptive Pill (ECP) Users from Namuna Medical - Pandey, Naranath (Madhyabindu Journal, 2025)
Unintended pregnancy occurs due to incorrect or inconsistent use of contraceptive methods. Such pregnancy can financially burden the family, society, and the nation. This study explored the knowledge, attitudes, and practices of ECP users from Namuna Medical Kawasoti Nawalpur. The study was conducted based on a convenience sampling method of 117 respondents who came to Namuna Medical to purchase ECP using a structured questionnaire. Furthermore; Demographic characteristics of ECP users, their knowledge, attitudes, and practices were studied. Data were analyzed using SPSS based on descriptive and mixed methods. About 47 percent of the respondents had good practice in using ECP. The general awareness level of ECP was 42.73 percent. However, knowledge about how to use ECP was low and misinformation among these users was high. Knowledge varied by source of information: informal sources were associated with misinformation, while sources of information from the medical field were associated with good knowledge. However, ECP users generally had a positive view of ECP (56.41 percent) and believed that ECP is safe. Those with adequate knowledge about ECP typically showed favourable attitudes towards ECP. 49.57 percent of users have consulted their friends and used ECP. These users were at risk because they had low awareness of ECP and still lacked knowledge in practice. Strategies to promote the use of ECP should focus on disseminating accurate information through relevant medical information sources to achieve a reliable and better understanding of ECP.